Modulating Anxiety and Functional Capacity with Anodal tDCS Over the Left Dorsolateral Prefrontal Cortex in Primary Dysmenorrhea - Dutra LRDV; Pegado R; Silva LK; da Silva Dantas H; Câmara HA; Silva-Filho EM; Correia GN; Micussi MTABC (Dove Medical Press, 2020)
Larissa Ramalho Dantas Varella Dutra,1 Rodrigo Pegado,2 Luana Karyne Silva,2 Hégila da Silva Dantas,2 Hialison Andrade Câmara,2 Edson Meneses Silva-Filho,2 Grasiéla Nascimento Correia,2 Maria Thereza Albuquerque Barbosa Cabral Micussi1 1Health Science Center, Federal University of Rio Grande do Norte, Rio Grande do Norte, Brazil; 2Graduate Program in Rehabilitation Science, Federal University of Rio Grande do Norte, Rio Grande do Norte, BrazilCorrespondence: Edson Meneses Silva-FilhoFaculdade de Ciências da Saúde do Trairi - Universidade Federal do Rio Grande do Norte, FACISA/UFRN, Rua Teodorico Bezerra, Santa Cruz, RN 59200-000, BrazilTel +55 81 99470 6661Email meneses.edson@yahoo.com.brBackground: Primary dysmenorrhea is a common and often debilitating condition affecting 40– 90% of menstruating women. This condition reduces functionality, quality of life, and social activities. Transcranial direct current stimulation (tDCS) has been used in many chronic pain syndromes, with evidence of improved pain, functionality, and mood in women with primary dysmenorrhea. The objective of this study was to determine whether tDCS could offer clinical benefits on pain, anxiety, affectivity, and functionality in women with primary dysmenorrhea.Methods: This parallel, sham, randomized, double-blind trial was conducted with 26 women randomized into sham tDCS and active tDCS. Anodal tDCS was applied for 5 consecutive days over F3 corresponding to the left dorsolateral prefrontal cortex (DLPFC) and the cathode electrode over Fp2 for 20 min with an intensity of 2 mA. A numeric rating scale (NRS) was used to assess pain, anxiety, positive and negative affect, and submaximal aerobic performance during two consecutive menstrual cycles.Results: No significant interaction was found between intervention and time on the NRS [F(2,44) = 1.358, p =  0.26], and a signiﬁcant main effect of time [F(2,44) = 4.446, p =  0.01] was found. The active group showed a significant reduction in anxiety (p =  0.03) with a mean difference of 5.12 (95% CI 0.79 to 11.05). No significant differences in positive and negative affect were found (p =  0.95 and p =  0.15, respectively). Submaximal aerobic performance was significantly greater in the active group [F(2,21) = 5.591, p =  0.02], with a mean difference of 70.87 (95% CI 8.53 to 133.21).Conclusion: Anodal tDCS over the DLPFC seems to be an effective therapeutic approach for improving anxiety and functionality in women with primary dysmenorrhea.Keywords: non-invasive brain stimulation, menstrual cycle, pain, anxiety, functional capacity